2022
DOI: 10.30541/v47i4iipp.711-726
|View full text |Cite
|
Sign up to set email alerts
|

Telecommunication Infrastructure Development and Economic Growth: A Panel Data Approach

Abstract: World is going to be global village due to the introduction of new and advanced technology and new innovations in technology make it more possible day by day. The widely spread economic activities both in real as well as in credit market is possible when they use advance technology to communicate. This is a fact that the world is rapidly moving towards an economic system based on the continuous and ubiquitous availability of information. Developing countries try to maintain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
1

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 20 publications
2
22
0
1
Order By: Relevance
“…This study identified the following components of network sharing that can be shared by Mobile Service Providers: Antennae, Feeder cables, Node B and Transmission equipment. This findings reinforce a similar study that was conducted by [4] who noted that the core network elements of which antenna is part of should not be shared, so that each service provider can maintain control their equipment. 16 out of 39 respondents from Safaricom (41%), 10 out of 17 respondents from Airtel (59%) and 12 out of 15 respondents from Orange (80%) agreed that feeder cables could be shared in an open ICT infrastructure sharing framework.…”
Section: Research Findings and Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…This study identified the following components of network sharing that can be shared by Mobile Service Providers: Antennae, Feeder cables, Node B and Transmission equipment. This findings reinforce a similar study that was conducted by [4] who noted that the core network elements of which antenna is part of should not be shared, so that each service provider can maintain control their equipment. 16 out of 39 respondents from Safaricom (41%), 10 out of 17 respondents from Airtel (59%) and 12 out of 15 respondents from Orange (80%) agreed that feeder cables could be shared in an open ICT infrastructure sharing framework.…”
Section: Research Findings and Discussionsupporting
confidence: 78%
“…According to [5], ICT Infrastructure incorporates site sharing, network sharing and spectrum sharing. In Node B Sharing, Radio network controller (RNC) and Core Network are not shared in this model, so that each service provider can maintain control of their equipment and spectrum use [4]. According to [19], the separation of the Core Networks also allows each service provider to offer differentiated services to their subscribers.…”
Section: A Theoretical and Conceptual Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, [10,102,119,132] support the validity of growth-led ICT hypothesis (i.e., a demand-following hypothesis e DFH). Moreover [22,23,33,34,73,103,107,116,124,125], find existence of a mutual causal relationship between the two variables (i.e., they support a feedback hypothesis e FBH). Finally, some studies find a complete lack of a causal relationship between the variables -or a null hypothesis (NLH).…”
Section: Ict Infrastructure and Economic Growthmentioning
confidence: 96%
“…The idea behind this argument, which is in favour of the bidirectional causality, is that telecommunications infrastructure is indispensable to economic growth and economic growth inevitably requires a solid telecommunications infrastructure (Cronin et al 1993a;Nandi 2003, 2011;Yoo and Kwak 2004;Zahra et al 2008;Ramlan and Ahmed 2009;Pradhan et al 2013b).…”
Section: Telecommunications Infrastructure and Economic Growth 403mentioning
confidence: 99%